2021
DOI: 10.3390/agronomy11020325
|View full text |Cite
|
Sign up to set email alerts
|

Gluten Protein Compositional Changes in Response to Nitrogen Application Rate

Abstract: Field trials were conducted to evaluate the effect of nitrogen level on wheat protein content and composition in 16 cultivars over two years at three locations. The nitrogen treatment comprised two nitrogen levels, 0 kg ha−1 as low and 100 kg ha−1 as high nitrogen, applied as top dressings of 50 kg nitrogen per ha at tillering and stem extension growth stages. Increased nitrogen level generally enhanced grain protein by 11.3% (11.5% vs. 12.8%). Considering protein composition determined by reversed phase–high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
5
11
0
Order By: Relevance
“…Firstly, we analysed the protein and gluten content and gluten index in winter wheat lines under control (no nitrogen applied) and high nitrogen (120 kg N·ha −1 ). Statistically significant differences were found for the main factors (winter wheat lines, N level) which are in accordance with the results of other authors [ 48 , 49 , 50 , 51 ]. We found that the nitrogen dose was a primary source of protein and gluten content variation.…”
Section: Discussionsupporting
confidence: 92%
“…Firstly, we analysed the protein and gluten content and gluten index in winter wheat lines under control (no nitrogen applied) and high nitrogen (120 kg N·ha −1 ). Statistically significant differences were found for the main factors (winter wheat lines, N level) which are in accordance with the results of other authors [ 48 , 49 , 50 , 51 ]. We found that the nitrogen dose was a primary source of protein and gluten content variation.…”
Section: Discussionsupporting
confidence: 92%
“…Consequences on yield and kernel weight are significant ( Djanaguiraman et al, 2020 ), being early grain filling associated with photosynthesis ( van Dongen et al, 2004 ) and late grain filling with the remobilization of stored assimilates from vegetative tissues to the grain ( Plaut et al, 2004 ). In our study, however, no differences in total amount of proteins were detected in seed samples derived from different years or periods, and kernels resulted in a mean protein content of 13.1% of total weight, in accordance with the values found in the literature for the San Pastore cultivar, i.e., 12.7 and 11.6% ( Hristov et al, 2010 ; Horvat et al, 2021 ). The grain-filling stage might be crucial for the accumulation of gluten proteins, a complex process involving a finely tuned spatial and temporal regulation; so, the above-mentioned environmental changes might determine the changes also in gluten composition.…”
Section: Discussionsupporting
confidence: 92%
“…The grain-filling stage might be crucial for the accumulation of gluten proteins, a complex process involving a finely tuned spatial and temporal regulation; so, the above-mentioned environmental changes might determine the changes also in gluten composition. The gluten fraction, i.e., gliadins and glutenins, constitutes the 80–85% of total grain proteins and contributes to rheological, pasting, and textural properties of dough ( Shewry et al, 1995 ; Horvat et al, 2021 ). Hence, amount of protein, protein distribution among fractions, and the ratio between gliadins/glutenins and HMW-GS/LMW-GS in wheat flours derived from San Pastore kernels harvested in different years, from both before and after CC periods, were tested for correlation with CGDDs accumulated in the period 1 May–15 June, when wheat grain filling typically occurs in this area.…”
Section: Discussionmentioning
confidence: 99%
“…A higher Gli/Glu ratio may suggest a reduced technological quality of the protein of wheat cultivars; as the number of glutenin subunits is positively correlated with the energy and volume of bread dough, a higher Gli/Glu ratio lowers the value of these parameters [66]. Many authors [58,59,64,65] indicate a significant impact of the environmental conditions, including weather conditions, on the content of gliadins and glutenins and their subunits, which was also confirmed in the present authors' study. A more favorable composition of the glutenin proteins and their HMW/LMW subunits was demonstrated especially in the grain of cv.…”
Section: Protein Fraction Compositionsupporting
confidence: 86%
“…In a study by Stępie ń and Wojtkowiak [64], the use of organic fertilization and meat and bone meal (MBM) resulted in a significant increase in the subunits α/β and γ gliadins in the grain of wheat cultivars. Horvat et al [65] showed that the composition of the gliadin and glutenin fractions in grains is determined mainly by the genetic traits of wheat cultivars rather than differentiated nitrogen fertilization. In the present authors' study, the highest values of the γ gliadin protein fractions, as well as LMW and HMW glutenins in the CONV system compared to INTEG, were found in the grain of cv.…”
Section: Protein Fraction Compositionmentioning
confidence: 99%